The argonaut constructs its shell via physical self-organization and coordinated cell sensorial activity - Antonio G. Checa (Elsevier, 2021)
Summary: The shell of the cephalopod Argonauta consists of two layers of fibers that elongate perpendicular to the shell surfaces. Fibers have a high-Mg calcitic core sheathed by thin organic membranes (>100 nm) and configurate a polygonal network in cross section. Their evolution has been studied by serial sectioning with electron microscopy-associated techniques. During growth, fibers with small cross-sectional areas shrink, whereas those with large sections widen. It is proposed that fibers evolve as an emulsion between the fluid precursors of both the mineral and organic phases. When polygons reach big cross-sectional areas, they become subdivided by new membranes. To explain both the continuation of the pattern and the subdivision process, the living cells from the mineralizing tissue must perform contact recognition of the previously formed pattern and subsequent secretion at sub-micron scale. Accordingly, the fabrication of the argonaut shell proceeds by physical self-organization together with direct cellular activity.